(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
This experience report describes the implementation of an extension project carried out by students of the Civil Engineering course at the Universidade do Estado de Minas Gerais (UEMG), Passos-MG campus, with the objective of promoting interaction between the university and the local community through the use of technologies applied to civil construction. The project involved the creation of electronic models using Revit software and the construction of physical models, which were exhibited to the public in the city square, providing a more accessible and visual understanding of the stages of an architectural project. The activity aimed to stimulate the interest of young people in the areas of engineering and architecture, while offering students the opportunity to apply technical concepts in practical situations, promoting the development of professional and social skills. The results indicated a positive impact both for the community, by democratizing technical knowledge, and for the students, who improved their skills in the area of civil construction and strengthened their bond with society.